Penetapan Harga Ikan di Pasar Kuala Batahan - Usin, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is entitled Fish Price Determination at Kuala Batahan Market, Batahan District, Mandailing Natal Regency in terms of the Compilation of Islamic Economic Law. Researchers are interested in this problem because fish sellers charge a price that is higher than the usual market price to buyers who come from outside the batahan area. This research was conducted at the Kuala Batahan market, Batahan sub-district, Mandailing Natal district. The research subjects are fish traders in the Kuala Batahan market, while the object of this research is the pricing mechanism for fish traders in the Kuala Batahan market. The method used in data collection is observation, interviews and documentation. In this writing technique using descriptive methods of primary data and secondary data. After this research was conducted and analyzed, that the fish sellers in the Kuala Batahan market sell similar fish to buyers at different prices to buyers from outside the Batahan area with buyers from the area to seek greater profits. The buying and selling system they apply is a direct buying and selling system, the seller offers to the buyer and the buyer pays directly to the seller, while to find out that prospective buyers from outside the area are seen from the way they dress neatly and drive luxuriously. In the view of the Compilation of Sharia Economic Law on buying and selling fish at the Kuala Batahan Market, Batahan District, Mandailing Natal Regency, it has fulfilled the legal pillars and conditions of buying and selling, but the way they sell fish to buyers from outside the area is contrary to the Compilation of Sharia Economic Law Article 33 fraud, there is an element of Tadlis that oppresses one of the parties, namely the buyer.